Strengthening Capacity for Participatory Development - Cohen, Marc J.; Garrett, James L.; Rocchigiani, Mariagrazia (International Food Policy Research Institute, 2008)
Capacity development is essential to participatory initiatives, especially given the recent trend toward decentralized governance in many developing countries. Communities need both the wherewithal to carry out development activities themselves, and the capability to make demands of government officials and service providers. Programmes that support local capacity development and community participation must take local needs and institutions into account, and provide an enabling environment for community action..